Inkonsistensi Pertimbangan Hakim terhadap Alat Bukti Elektronik dalam Perkara Perdata - Fitrah Maryam P.Z; Frasisi Wulandari; Retno Wulandari; Sri Handayani (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of information and communication technology has changed the paradigm of proof in civil cases, where the interaction of the parties is now mostly carried out through electronic media such as instant messages, electronic mails, and digital documents. This condition places electronic evidence as an important instrument in the practice of civil justice. Normatively, the recognition of electronic evidence has been affirmed in Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Law), which states that electronic information, electronic documents, and their printed results are legal evidence. However, the application of these norms has not been completely consistent in civil justice practice. The assessment of the evidentiary strength of electronic evidence is still highly dependent on the discretion of judges, as there are no detailed technical guidelines regarding assessment standards, relevance, and adequacy. This inconsistency can be seen in a comparison of the Magelang District Court Decision Number 18/Pdt.G/2023/PN Mgg and the Decision of the Lolak Religious Court Number 3/Pdt.G/2022/PA. Llk, which shows the difference in the judge's approach in assessing electronic evidence. This study uses a normative juridical method with a legislative approach and decision analysis. The results of the study emphasized the need for reform of civil procedure law and the preparation of clear technical guidelines to realize uniformity and legal certainty in the assessment of electronic evidence.